PENGARUH KEBIJAKAN PEMERINTAH TERHADAP PENDAPATAN DAERAH DARI ALKOHOL AREN (CAPTIKUS) DI SULAWESI UTARA - David Ronald Talumewo; Wenny Tilaar; Agnes Loho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
Alkohol Aren is commodity consumtion of North Sulawesi with behaviour trade market. It have policies government with taxes, permission, retribution make impact for income regional. Topics is the impact of government policy on alcohol aren regional income in North Sulawesi. This research aimed to analyze government policy impact on alcohol aren production, alcohol industry, etanol industry and alcohol demand of people.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Time series data from 2013-2018 were sourced from the Service of Plantation, the Statistics Central Agency (BPS), Trading Regulatory Agency (Deprindag), the World Bank, The Industry product Casanova and Segaran Sari. Simultaneous equations, consisting of 11 equations (9 structural equations and 2 identity equations) and estimated by Two Stage Least Squares (2SLS) method with SAS 9.1 application.Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Regional income has effect from taxes, taxes has effect from minol production, minol production has effect from â€œcaptikusâ€ production or alcohol aren production and sum of industry, captikus production has effect from price of captikus and price of minol, price of captikus has effect from minol demand. Price of Minol has effect captikus production and alcohol aren demand, alcohol aren demand has effect minol demand, minol demand has effect from minol price and supply minol, the last supply minol has effect from stock.Keywords: Alkohol Aren, Demand and Supply, production, Quantiti tax, GDPR, simultaneous equations